New Operation Strategy for a Grid-Connected Three-Phase Three-Level NPC qZS Inverter Based on Power Losses - Roncero-Clemente, Carlos; Romero-Cadaval, Enrique; Husev, Oleksandr; Martins, Joao (Elektronika ir Elektrotechnika, 2016)
This paper proposes a new operation strategy for a three-phase three-level neutral-point-clamped quasi-impedance source inverter in a grid-connected mode. The strategy is intended for any inverter based on impedance source networks where the shoot-through states allow a wider input operation range. This feature is commonly requested in photovoltaic applications due to variations in the level of irradiance. Converters of that family have different control variables or degrees of freedom that can be used to boost the input voltage. In the first step, focus was on possible control variables for the design of the control strategy to regulate the active/reactive power. We used a power losses analysis to determine the most suitable variables in each input voltage interval. Our detailed description for the design of the control strategy is based on the well-known relationship in an electrical system between P-d and Q-V. Good performance of the full system was validated by simulations. DOI: http://dx.doi.org/10.5755/j01.eie.22.3.15316